The relationships between short video addiction, subjective well-being, social support, personality, and core self-evaluation: a latent profile analysis - Jie Ding; Ziyu Hu; Yichen Zuo; Yawen Xv (BMC Public Health)
Abstract Background The proportion of short video addiction (SVA) is increasing among different populations, and its impact on the adolescent group has attracted research attention in recent years. To better explore the heterogeneity of individuals addicted to short videos and the antecedents of their addiction, the present study used quantitative research to conduct a latent profile analysis (LPA) of college students’ SVA from the perspective of internal and external resources. Methods Referring to the Interaction of Person-Affect-Cognition-Execution (I-PACE) theory, this study explores the relationship between subgroups of SVA on the one hand and subjective well-being (SWB), social support (SS), core self-evaluation (CSE), and extraversion on the other using latent profile analysis. The research participants consisted of 694 college students aged between 18–25 years. The research tools used were the SVA Scale for College Students, Subjective Well-Being Scale, Perceived Social Support Scale, Core Self-Evaluation Scale, and the Big Five Personality Traits Scale. Results The results revealed three subtypes of adolescent SVA: high (28.8%), medium (56.6%), and low (14.6%), demonstrating significant heterogeneity among groups. These groups also showed significant differences in terms of their internal and external resource scores. Specifically, the high-addiction group scored significantly lower on extraversion and SS than the other two groups. The medium-addiction group had the lowest score on CSE among the three groups. The low-addiction group scored significantly higher on SS, CSE, and SWB compared with the high-addiction and medium-addiction groups. Conclusion This study reveals that students with low extraversion, low SS and CSE scores tend to become addicted to short videos. SVA has negatively affected these personal traits. Our study explored the heterogeneity of SVA among college students from an individual-centered perspective, providing empirical support for scientifically and reasonably guiding the use of short videos among college students.